BMP9 promotes bone differentiation of bone marrow mesenchymal stem cells via Orai1 pathway - ZHOU Jia-wang, LU Guo-hai, LI Xiao-lin (Jichu yixue yu linchuang, 2021)
Objective To explore the role of calcium release activated calcium channel protein 1 (Orai1) in bone marrow mesenchymal stem cells (BMSCs) osteogenesis induced by bone morphogenetic protein 9 (BMP9). Methods BMSCs were isolated by adherent method, and the third generation BMSCs were treated with 10－5mol/L of BMP9, and the mRNA expression of Orai1 was measured at different time points. RT-qPCR and Western blot were used to value the transfection efficiency after Orai1 knockdown. The osteogenic markers of Runx2, OPN and OCN were detected by RT-qPCR. Hydroxyapatite/PLA/chitosan, a scaffold material for bone tissue engineering, was implanted into the subcutaneous of nude mice. After 4 weeks, the osteogenic effect was examined by microscopy. Results The mRNA expression of Orai1 increased gradually at the 5th day after BMP9 induction (P＜0.05). The gene and protein expression of Orai1 decreased significantly after Orai1 knockdown (P＜0.05). Besides, the osteogenic effect of Orai1 knockdown decreased significantly, and the expression of Runx2, OPN and OCN gene decreased significantly (P＜0.05). Moreover, BMP9 could significantly improve the ectopic osteogenic ability of BMSCs, and Orai1 knockdown significantly inhibited this effect (P＜0.05). Conclusions BMP9 plays an important role in osteogenic differentiation of BMSCs potentially by regulating Orai1.